PERBEDAAN GAYA BELAJAR SERTA IMPLIKASI TERHADAP MINAT BELAJAR SISWA DI KELAS VII SMP NEGERI 12 KOTA JAMBI - Siti Ammara Hasifa; Dwi Navisha; Gilang Nur Karim Alviansyah; Reza Laiman Putra; Wardi Syafmen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the differences in learning styles (visual, auditory, and kinesthetic) and their implications for students' learning interests, while also analyzing the accompanying psychological conditions in the form of anxiety in mathematics learning. This descriptive quantitative study was conducted in grade VII of SMP Negeri 12 Jambi City with a total sample of 25 students. Data collection used a structured questionnaire instrument consisting of 30 statements to measure the level of anxiety and interest tendencies based on learning style preferences. The results of descriptive data analysis showed that the total actual score obtained from all respondents was 2,564 out of a maximum ideal score of 3,750. Through quantitative percentage calculations, the final index value was obtained at 68.37%. Based on empirical categorization standards, it can be concluded that the level of anxiety in mathematics learning in students is in the Moderate category. The implications of this finding indicate the need for a variety of learning strategies that can accommodate the diversity of student learning styles in order to minimize psychological anxiety and simultaneously boost interest in learning mathematics in the classroom.